Do Family-Controlled Malaysian Firms Create Wealth for Investors in the Context of Corporate Acquisitions? - Ling, L.; Evans, John; Shaikh, J.; Sadique, Md Shibkey (2014)
Evidence has proved that family-controlled firms are prevalent in Malaysia and do exert considerable economic power in the country. Two possible scenarios emerge when ownership of firms become concentrated in the hands of only a few shareholders or a group of related shareholders. Firstly, the interests of related shareholders could be aligned with other non-family shareholders (Agency Problem I). Conversely, there is a possibility that related shareholders could treat themselves preferentially over the minority shareholders (Agency Problem II). Given that the ownership structures of the majority of Malaysian publically listed firms are characterised by concentrated shareholdings, protection of the interests of minority shareholders becomes critical. However, beyond anecdotal evidence, there is little empirical evidence on the relevance of minority expropriation activities to Malaysian family-controlled firms and firm value. This study investigates the corporate acquisition activities of family-controlled Malaysian firms. Corporate acquisitions are amongst the high profile corporate investment mechanisms that provide a direct measure for possible expropriation of shareholder funds or value-enhancing activities. This study used classical event study methodology to examine the wealth created by corporate acquisition activities of family-controlled Malaysian firms. The findings of this study found that whilst family ownership improved firm value, it could be destructive if power is entrenched by a few. The implications, especially for Malaysian policy makers, include determination of additional corporate governance framework and governmental effort to hinder concentrated family ownership in family-controlled firms. As highlighted by OECD (The Star, 2013), poor enforcement of corporate governance compliance requirements remains an issue for Malaysia.